The Course of Self-Efficacy for Therapeutic Use of Self in Norwegian Occupational Therapy Students: A 10-Month Follow-Up Study - Kathrin Schwank; Tove Carstensen; Farzaneh Yazdani; Tore Bonsaksen (Occupational Therapy International)
Background. Occupational therapy students need to develop self-efficacy for managing the therapeutic relationship in practice. This study examined the 10-month trajectories of Norwegian students’ self-efficacy for use of self. Methods. Eighty-nine students completed self-efficacy questionnaires related to the use of self after a workshop and at 3- and 10-month follow-up. Changes on the three outcome measures (self-efficacy for therapeutic mode use, for recognizing clients’ interpersonal characteristics, and for managing interpersonal events) were analyzed with repeated measures ANOVA. Results. Across the follow-up period, the students improved their self-efficacy for therapeutic mode use (partial η2 = 0.44, p<0.001), for recognizing clients’ interpersonal characteristics (partial η2 = 0.81, p<0.001), and for managing interpersonal events (partial η2=0.32, p<0.001). Conclusion. The increased self-efficacy for use of self that was found at 3-month follow-up was maintained at 10-month follow-up. The results indicate that students may experience a boost in self-efficacy for therapeutic use of self after a brief workshop and that these changes can be sustained over time.